An Investigation of the Effects ofCationic Conditioning Systems onHair Combability and SensoryPerformance (Aintelia Science Notes, 2026)
In this study, the surface interactions of cationic surfactant-based conditioningsystems on hair fibers and the resulting performance outcomes werecomprehensively evaluated. The negatively charged surface characteristics of hairfibers, particularly after washing, facilitate the adsorption of cationic agents onto thehair surface via electrostatic attraction. As a result of this adsorption mechanism, alow-friction film layer is formed on the hair surface, reducing inter-fiber interactionforces and improving combability performance. Within the scope of the study,formulations containing cationic conditioning systems were comparatively evaluatedagainst reference systems, and all formulations were standardized based on anequivalent active matter concentration of 2%. Wet and dry combing performancewas assessed using a texture analyzer by measuring combing force values. Sensoryevaluations were conducted by trained panelists under a blind test protocol andscored using a multi-parameter approach. The findings demonstrated that cationicsystems form a homogeneous and stable film layer on the hair surface, significantlyreducing the coefficient of friction and markedly improving both wet and drycombability. Furthermore, a strong correlation was observed between sensoryevaluation results and instrumental measurements. In conclusion, cationicsurfactant-based conditioning systems provide high-performance and sensoriallyoptimized solutions in modern hair care formulations.
Keywords: hair combing test; hair fiber